Anti-inflammatory activity of surface layer protein SlpA of Lactobacillus acidophilus CICC 6074 in LPS-induced RAW 264.7 cells and DSS-induced mice colitis. (December 2018) - Cai, Zhendong; Xu, Puxu; Wu, Zhen; Pan, Daodong
Graphical abstract: Highlights: SlpA reduces the production of inflammation mediators in LPS-induced RAW 264.7 cells. SlpA inhibits LPS-induced TLR4-related signaling activation. SlpA attenuates NLRP3- and NOD2-related signaling activation triggered by LPS. SlpA ameliorates DSS-induced colitis in mice. Abstract: Lactobacilli have beneficial effects on the digestive and immune systems. Surface layer protein SlpA is a key factor in probiotic–host crosstalk; however, how this immunomodulation affected by Lactobacillus SlpA is not yet well understood. In a LPS-induced RAW 264.7 cell model, SlpA derived from Lactobacillus acidophilus CICC 6074 significantly reduced the inflammatory responses as evidenced by inhibition of the production of inflammatory mediators such as iNOS and COX-2 and inflammatory cytokines, including TNF-α, IL-10, IL-1β, IFN-α and IFN-β, which may associate with TLR4-dependent MAPK and NF-κB as well as intracellular NOD2- and NLRP3-related signaling inactivation. Most importantly, SlpA ameliorates DSS-induced mice colitis indicated by reduced colitis symptoms including body weight loss, colonic atrophy and colonic mucosal damage, which may owe to a decrease in inflammatory cytokines. These findings suggest that SlpA has an ameliorative effect on the inflammation response and therefore a potential therapeutic role in treating colitis.